Properties of Concrete using Tanjung Bin Power Plant Coal Bottom Ash and Fly Ash - Abubakar, Abdulhameed Umar; Baharudin, Khairul Salleh (International Journal of Sustainable Construction Engineering and Technology, 2012)
Coal combustion by-products (CCPs) have been around since man understood that burning coal generates electricity, and its utilization in concrete production for nearly a century. The concept of sustainable development only reawaken our consciousness to the huge amount of CCPs around us and the need for proper reutilization than the current method of disposal which has severe consequences both to man and the environment. This paper presents the result of utilization of waste from thermal power plants to improve some engineering properties of concrete. Coal bottom ash (CBA) and fly ash were utilized in partial replacement for fine aggregates and cement respectively. The results of compressive strength at 7, 28, 56 & 90 days curing are presented because of the pozzolanic reaction. Other properties investigated include physical properties, fresh concrete properties and density. The results showed that for a grade 35 concrete with a combination of CBA and fly ash can produce 28 day strength above 30 MPa.